122k views
5 votes
Simplify the rational expression. state any restrictions on the variable. n4-10n^2+24/n^4-9n^2+18

2 Answers

6 votes

1. Factor expression
n^4-10n^2+24:


n^4-10n^2+24=(n^2-4)(n^2-6)=(n-2)(n+2)(n-√(6))(n+√(6)).

2. Factor expression
n^4-9n^2+18:


n^4-9n^2+18=(n^2-3)(n^2-6)=(n-√(3))(n+√(3))(n-√(6))(n+√(6)).

Note that


n\\eq √(3),\\n\\eq -√(3),\\n\\eq √(6),\\n\\eq -√(6),

because this expression is placed in the denominator.

3. Now


(n^4-10n^2+24)/(n^4-9n^2+18)=((n-2)(n+2)(n-√(6))(n+√(6)))/((n-√(3))(n+√(3))(n-√(6))(n+√(6)))=\\ \\=((n-2)(n+2))/((n-√(3))(n+√(3)))=(n^2-4)/(n^2-3).

User Fu Xu
by
5.2k points
3 votes

ANSWER


(n^4-10n^2+24)/(n^4-9n^2+18)=((n-2)(n+2))/((n-√(3))(n+√(3)))

For


n\\e \pm√(3)


Step-by-step explanation


We have
(n^4-10n^2+24)/(n^4-9n^2+18)


This is very easy to simplify. We shall look at the two expressions from a quadratic trinomial perspective.


We rewrite the rational expression to obtain;



(n^4-10n^2+24)/(n^4-9n^2+18)=((n^2)^2-10(n^2)+24)/((n^2)^2-9(n^2)+18)


We can now see that both the numerator and denominator are quadratic trinomials in
n^2.


We split the middle terms as follows;



(n^4-10n^2+24)/(n^4-9n^2+18)=((n^2)^2-6n^2-4n^2+24)/((n^2)^2-6n^2-3n^2+18)




(n^4-10n^2+24)/(n^4-9n^2+18)=(n^2(n^2-6)-4(n^2-6))/(n^2(n^2-6)-3(n^2-6))


We factor further to obtain;


(n^4-10n^2+24)/(n^4-9n^2+18)=((n^2-6)(n^2-4))/((n^2-6)(n^2-3))


We now cancel out common factors to get;



(n^4-10n^2+24)/(n^4-9n^2+18)=((n^2-4))/((n^2-3))




(n^4-10n^2+24)/(n^4-9n^2+18)=((n-2)(n+2))/((n-√(3))(n+√(3)))

For


n\\e \pm√(3)


User Oluwafemi Sule
by
5.5k points